Annual Plan 1964-65 VoI. I Government of Himachal Pradesh - Planning Commission (Planning Commission, 1964)
The Planning Commission have approved a financial outlay of Rs. 239.68 lakhs for the various schemes to be executed by the Department of Agriculture during the Third Plan period. In this Plan, originally 61 schemes were included and subsequently some more were also added. of these schemes, 58 were put into operation during 1961-62 and eight more schemes were included during 1962-63.
Government of Himachal Pradesh, Planning and Development Department